PERBANDINGAN HASIL EFEK KARAKTER SETTINGAN MAKE-UP DENGAN PEWARNAAN BUATAN DAN PEWARNAAN ALAMI DARI BUAH BIT - Zahrani Sandya Arvita; Yunus Karyanto (Journal of Beauty and Cosmetology (JBC), 2024)
Makeup can also be interpreted as painting with facial skin media using cosmetic tools and materials. Everyone who makes up themselves or others wants to be seen by others so that the results are beautiful and satisfying. The developmentof the era is getting more advanced, many people are used to making up in every activity. Starting from everyday makeup, party makeup, and stage makeup.Research objectives: 1) To find out the results of the analysis of the use of artificial dyes in wound effect character makeup. 2.) To find out the results of the analysis of the use of natural beetroot dyes in the make-up of characters with woundeffects 3.) To describe the results of the comparative analysis of the application of artificial dyes and natural beetroot dyes in the make-up of characters with wound effects from the opinions of respondents.Research method Data collection using experiments, documentation, questionnaires The research population is PVKK students from the 2020 UNIPA class, The research sample is 40 people, the analysis technique used is the two- sample t-statistical test. The result is there is a comparison of the results between the use of artificial dyes and natural beetroot dyes wound effect character. The results of the analysis are that most respondents agree that the use of natural beetroot dyes is satisfactory, although half of some of them do not like the application of artificial dyes to produce cut wounds.The second result is a comparison of the results of natural dyes and natural beetroot dyes and artificial dyes, namely the results below 0.05, namely below 0.05 means h 0 is rejected and ha is accepted, which means that there is a comparison in the results.The third result is the authenticity of the blood color, the concentration of the red color, and the color produced is thick.